Component-based model of buckling panels of steel beams at elevated temperatures. (March 2016) - Quan, Guan; Huang, Shan-Shan; Burgess, Ian
Abstract: Both bottom-flange buckling and beam-web shear buckling have been observed in many full-scale fire tests in the vicinity of beam-to-column connections. These phenomena can influence the load redistribution within the adjacent connections and the global structural behaviour, detrimentally affecting the structural overall fire resistance. However, existing models for bottom-flange buckling overestimate the structural resistance when the beam is slender. In this work, a new analytical model has been created to predict both of these types of buckling behaviour in steel beams in the vicinity of beam-to-column connections at elevated temperatures. The model considers the individual effects of both buckling modes, as well as their interaction. It is capable of predicting the force–deflection relationship of the buckling zone from the initial elastic loading stage to run-away failure. The new analytical model has been compared with the existing Dharma's model and a range of 3D finite element simulations created using the ABAQUS software. Comparisons have shown that the proposed method gives better predictions than Dharma's model. A component-based model of the buckling zone has been created on the basis of this new analysis. The component-based model can provide sufficient accuracy, and will be implemented in the software Vulcan for performance-based global structural fire analysis. Graphical abstract: Highlights: Analytical model to investigate on local buckling of Classes 1 to 2 steel beams in fire. Bottom-flange buckling and beam-web shear buckling can be considered separately. The proposed model provides upper bound compared with validated FE models. The proposed model provides better results compared Dharma's model. Component-based model of the buckling panel has been developed.